1992
DOI: 10.1111/j.1471-4159.1992.tb10040.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Structural and Functional Characterization of Mouse Myelin/Oligodendrocyte Glycoprotein

Abstract: The myelin/oligodendrocyte glycoprotein (MOG) is found exclusively in the CNS, where it is localized on the surface of myelin and oligodendrocyte cytoplasmic membranes. The monoclonal antibody 8-18C5 identifies MOG. Several studies have shown that anti-MOG antibodies can induce demyelination, thus inferring an important role in myelin stability. In this study, we demonstrate that MOG consists of two polypeptides, with molecular masses of 26 and 28 kDa. This doublet becomes a single 25-kDa band after deglycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
1
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 37 publications
4
55
1
2
Order By: Relevance
“…It has been reported that it is involved in the formation of the intraperiod line of myelin [25], and the results from the knockout and transgenic mice also suggest an important role of PLP in the interaction of oligodendrocyte and axon [25,26]. On the other hand, MOG is a quantitatively minor component of the CNS myelin that represents only ~0.05% of the total protein content of myelin [27]. It is located at the extracellular surface of myelin sheaths and oligodendrocyte processes and is believed to regulate oligodendrocyte microtubule stability and mediate interactions between the myelin and the immune system [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that it is involved in the formation of the intraperiod line of myelin [25], and the results from the knockout and transgenic mice also suggest an important role of PLP in the interaction of oligodendrocyte and axon [25,26]. On the other hand, MOG is a quantitatively minor component of the CNS myelin that represents only ~0.05% of the total protein content of myelin [27]. It is located at the extracellular surface of myelin sheaths and oligodendrocyte processes and is believed to regulate oligodendrocyte microtubule stability and mediate interactions between the myelin and the immune system [28].…”
Section: Discussionmentioning
confidence: 99%
“…That this actually occurs in vivo has recently been shown for MBPp84 -102 in the context of HLA-DR2 (38). However, MBP is an abundant Ag in the CNS, whereas MOG comprises only 0.01-0.05% of the myelin mass (39). Therefore, it is not known whether it is processed and presented in the CNS, and by which type of APCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is exclusively localized on the outer surface of the myelin sheath, where it can be readily attacked by specific Ab mediating demyelination (5,6). In addition, the expression of MOG is restricted to the CNS, and it appears late during development of myelin (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%